The Lock and Key of Medicine : Monoclonal Antibodies and the Transformation of Healthcare - Marks, Lara, 1963- (Yale University Press, 2015)
The untold story of monoclonal antibodies-the molecular heroes of biotechnology that revolutionized the diagnosis and treatment of more than fifty major diseases This book is the first to tell the extraordinary yet unheralded history of monoclonal antibodies. Often referred to as Mabs, they are unfamiliar to most nonscientists, yet these microscopic protein molecules are everywhere, quietly shaping our lives and healthcare. Discovered in the mid-1970s in the laboratory where Watson and Crick had earlier unveiled the structure of DNA, Mabs have radically changed understandings of the pathways of disease. They have enabled faster, cheaper, and more accurate clinical diagnostic testing on a vast scale. And they have played a fundamental role in pharmaceutical innovation, leading to such developments as recombinant interferon and insulin, and personalized drug therapies such as Herceptin. Today Mabs constitute six of the world's top ten blockbuster drugs and make up a third of new introduced treatments. Lara V. Marks recounts the risks and opposition that a daring handful of individuals faced while discovering and developing Mabs, and she addresses the related scientific, medical, technological, business, and social challenges that arose. She offers a saga of entrepreneurs whose persistence and creativity ultimately changed the healthcare landscape and brought untold relief to millions of patients. Even so, as Marks shows, controversies over Mabs remain, and she examines current debates over the costs and effectiveness of these innovative drugs.